Investigating the Effect of Brand Certification on Brand Reputation with the Mediating Role of Brand Attitude and Consumers’ Awareness in Ansar Bank - AliAkbar Reeisi Sarteshnizi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research, we pursued to investigate the effect of brand certification on brand reputation with the mediating role of brand attitude and consumers’ awareness in the bank. For this purpose, regarding the research hypotheses and foundations, a conceptual model has been offered and in accordance with its dimensions, a researcher-made questionnaire has been prepared, that has been distributed among the desired population through two ways of customers’ club site and in-person. The research method was a survey of descriptive-analytical type, and two types of library and the use of electronic and field sources for data collection method in this research were applied. To analyze the questionnaire, having investigated its validity, the reliability ratio of questionnaires was calculated by 265 people and using Cronbach’s alpha formula, that was obtained 0.872 for its overall indicated the desirable level of reliability, and structural equation methods and partial least squares analysis were performed, using PLS software for testing hypotheses. Finally, considering the research hypotheses investigation and analysis, the impact ratio of each one of the variables was determined. The results show that all questions are significant and their impacts are considerable. According to the proposed model, brand certification as independent variable impacts all three main variables, and brand attitude, consumer awareness, and brand certification respectively have the highest impact on brand reputation as the dependent variable. Therefore, Ansar Bank should provide the ground and context of customers’ satisfaction through improving consumer attitude and awareness to improve its brand performance.